this is what i did:
i don't really know how to move to the next step in order to get something like (y-k)^2=4p(x-h) or (x-h)^2=4p(y-k)
it doesn't make sense cause i have the 4 outside which seems like its part of the 4p but (y-2) is squared.... and i can't complete the square on the right side since no x^2 value, only x.
thank you! I have another question, is that equivalent to this:
see it doesn't make sense because whats P? there is nothing infront of (x-1) such as 8(x-1) where in that case we could say 4p(x-1), p=2
it doesn't look like this general form (y-k)^2=4p(x-h) =/